Kinematic Analysis of a Dynamic Balance Task by Children Who Are Deaf. - Sabbatical Report - Martens, David (Spring;Exercise Science., 1998)
Keywords: dept.hms; faculty_collection; sabbatical_report

Development of Balance Performance Norms for the Biodex Balance System. - Finn, Joan (1997)
Keywords: dept.hms; faculty_collection; sabbatical_report

Physiological Indices of Elite Junior - I Alpine Skiers. - Axtell, Robert (1996)
Keywords: dept.hms; faculty_collection; sabbatical_report

Peak Performance Motion Analysis System. - Martens, David (1990)
Keywords: dept.hms; faculty_collection; sabbatical_report

(Here's Looking at You, 2000) - Ranker, H. Joseph (1990)
Keywords: dept.hms; faculty_collection; sabbatical_report

Growing Artificial Societies Social Science from the Bottom Up - Epstein, Joshua M.; Axtell, Robert (Complex adaptive systems, 1996)
How do social structures and group behaviors arise from the interaction of individuals? Growing Artificial Societies approaches this question with cutting-edge computer simulation techniques. Fundamental collective behaviors such as group formation, cultural transmission, combat, and trade are seen to "emerge" from the interaction of individual agents following a few simple rules. In their program, named Sugarscape, Epstein and Axtell begin the development of a "bottom up" social science that is capturing the attention of researchers and commentators alike. The study is part of the 2050 Project, a joint venture of the Santa Fe Institute, the World Resources Institute, and the Brookings Institution. The project is an international effort to identify conditions for a sustainable global system in the next century and to design policies to help achieve such a system. Growing Artificial Societies is also available on CD-ROM, which includes about 50 animations that develop the scenarios described in the text. Copublished with the Brookings Institution.
Keywords: Social sciences; dept.hms; faculty_collection

Academic preparation of athletic trainers as counselors - Misasi, S.P.; Davis Jr., C.F.; Morin, G.E.; Stockman, D. (Journal of Athletic Training, 1996)
Athletic trainers have assumed several roles and responsibilities over the years, but perhaps there is no more important role than that of a counselor. Are they prepared to do so? One hundred and thirty-two modified Revised Wylie Inventories were mailed to college/university athletic trainers to examine their educational preparation and experiences with counseling in various areas. Most athletic trainers surveyed reported that they were predominantly counseling in the areas of injury prevention, injury rehabilitation, and nutrition, and felt academically prepared to do so. However, it was reported that preparation to counsel in other less common areas (eg, family matters, financial matters, etc) was not adequately addressed in academic programs. The athletic trainers surveyed sought continuing education in order to meet the other counseling needs of student-athletes. Although they used several psychological referral services, it was apparent that most athletic trainers frequently served as counselors on many nonorthopedic topics. We suggest that athletic training educators consider incorporating both academic knowledge and clinical experience in a wider variety of counseling areas into their curricula.
Keywords: dept.hms; ⛔ No DOI found

Case study: Isokinetic rehabilitation of a ruptured biceps tendon - Martens, D.W.; Axtell, R.S.; Stofan, J.R. (Journal of Strength and Conditioning Research, 1995)
A 37-year-old male ruptured the distal biceps brachii tendon performing a gymnastics routine. At Week 8 postsurgery, a bilateral isokinetic test demonstrated a 64 and 50% (at 60° • s-1and 300° • s-1) peak torque deficit between uninjured and injured arms during elbow flexion. The subject participated in a concentric isokinetic exercise program 3 days a week for 4 months. At 1 year postsurgery a bilateral test demonstrated a 14% deficit in peak torque at 60° • s-1, and faster test velocities of 180° • s-1and 300° • s-1indicated higher torques for the injured biceps muscle. The rehabilitation program returned the ruptured biceps to a level of concentric strength nearly equivalent to the contralateral limb at the velocities tested. © 1995 National Strength & Conditioning Association.
Keywords: Avulsion; Bilateral; Specificity; Strength; dept.hms

Kinematic analysis of a dynamic balance task by children who are deaf - Butterfield, S.A.; Lehnhard, R.A.; Martens, D.; Moirs, K. (Clinical Kinesiology, 1998)
The purpose of this investigation was to identify dynamic balance strategies used by 18 boys and girls who were deaf. Each child was simultaneously videotaped from the frontal and sagittal planes while walking forward on a balance beam and stepping over a stick placed knee high. Next their performance was evaluated on a pass-fail basis. Following testing, each participant was assigned to the respective group (pass n = 9; fail n = 9) for kinematic analysis. Based on a discriminant function analysis of the data, head and trunk ranges of motion (ROM) were significant (p < .05) predictors of pass/fail performance. Children in the fail group had significantly greater head and trunk sway causing them to lose balance. Factors contributing to poor dynamic balance among children who are deaf are discussed as are implications for intervention and further research.
Keywords: Deaf; Dynamic balance; Proprioception; Vestibular; adolescent; article; child; clinical article; dept.hms; discriminant analysis; female; head movement; hearing impairment; human; male; proprioception; trunk; videotape; ⛔ No DOI found

Counseling Skills and the Athletic Therapist - Misasi, S.P.; Kemler, D.S.; Redmond, C.J. (Athletic Therapy Today, 1998)
Keywords: dept.hms

The effect of upper trapezius taping on electromyographic activity in the upper and middle trapezius region - Morin, G.E.; Tiberio, D.; Austin, G. (Journal of Sport Rehabilitation, 1997)
A characteristic of scapulothoracic dysfunction is the tendency for the upper regions of the trapezius to hypertrophy in relation to its middle and lower portions. This creates a muscular imbalance that can alter scapular position and subsequently the length-tension relationship of the shoulder muscles. Tape was applied over the right upper trapezius to inhibit electrical activity in the muscles of 10 uninjured subjects. EMG activity was recorded in two locations of the upper trapezius and one location in the middle to lower trapezius region while each subject maintained an isometric contraction designed to activate both muscles. With the tape applied, there was a statistically significant reduction in EMG activity of the upper trapezius with a corresponding increase in the middle/lower trapezius. The ability of the tape to alter trapezius activity in this fashion may help correct muscular imbalances in the trapezius muscle.
Keywords: article; controlled study; dept.hms; electromyography; human; human experiment; muscle isometric contraction; normal human; scapula; shoulder pain; trapezius muscle

Sport/leisure skill learning by adolescents with mild mental retardation: A four-step strategy - Yang, J.-J.; Porretta, D.L. (Adapted Physical Activity Quarterly, 1999)
Based on Singer's (1986) method, we investigated the effects of a four- step strategy (ready, look, do, score) on training, maintenance, and generalization of three closed skills (basketball free throw, overhand softball throw, and dart throw) by adolescents (M age = 17.2) with mild mental retardation (MR). A multiple baseline across skills design was used. Performances of 3 males and 3 females across these three skills were examined. Participants averaged a total of 46 sessions for the duration of the study. Results indicated that participants increased performance 18-56% across all three closed skills during the training phase. A total of 4 participants maintained performance on all three skills when reminders were present, and 2 decreased performance when the reminders were removed. All participants exhibited improved performance when a reinforcer was introduced. Moreover, 5 participants were able to generalize the four-step strategy to a different setting.
Keywords: adolescent; article; clinical article; coping behavior; dept.hms; female; human; learning; leisure; male; mental deficiency; physical performance; skill; sport

A study of breast cancer detection practices and beliefs in black women attending public health clinics - Duke, Suzanne S; Gordonsosby, Karen; Reynolds, Kim D; Gram, Inger T (Health Education Research, 1994)
In this study, breast cancer knowledge, beliefs and practices in low income black women were examined. First, focus groups were held with a total of 33 participants. Information gathered from the focus groups was used to develop a telephone survey which was partially based on the Health Belief Model (HBM) and administered to 92 subjects. Utilization rates of mammography and breast self-examination (BSE) were quite high; 66.3% of survey participants reported having at least one mammogram and 72.5% performed BSE. Because low-cost mammograms were available to the survey participants, these results suggest that women in this target population will utilize accessible and affordable mammograms. Several knowledge deficiencies that need to be addressed were also identified. Most of the health beliefs were not significantly associated with mammography or BSE utilization. Because the HBM has never been extensively tested on this population, its appropriateness as a behavior model for low-income women is examined. Implications for future research and interventions are discussed.
Keywords: *African Americans/px [Psychology]; *Breast Neoplasms/pc [Prevention & Control]; *Health Knowledge, Attitudes, Practice; Adult; Aged; Alabama; Blacks; Breast Neoplasms; Breast Neoplasms/eh [Ethnology]; Breast Neoplasms/px [Psychology]; Breast Self-Examination; Breast Self-Examination/px [Psychology]; Cohort Studies; Female; Human; Humans; Knowledge, Attitudes, Practice; Mammography; Mammography/px [Psychology]; Middle Age; Middle Aged; Support, U.S. Gov't, P.H.S.; adult; article; breast cancer; breast examination; cancer diagnosis; dept.hms; female; health survey; human; lowest income group; major clinical study; mammography; negro; outpatient department; priority journal; public health

Prognostic indicators for poor risk epithelial ovarian carcinoma - Rosman, Martin; Hayden, Cheryl L.; Thiel, Robert P.; Chambers, Joseph T.; Kohorn, Ernest I.; Chambers, Setsuko K.; Schwartz, Peter E. (Cancer, 1994)
Background. The objective of this study was to identify factors that categorize patients with epithelial ovarian carcinoma into favorable and unfavorable prognostic groups at the time of initial treatment. Methods. Data were analyzed from 51 women who were treated at Yale University, had an evaluable CA 125 half-life (t 0.5), and were followed for disease recurrence for at least 2 years. Results. Grade, maximum level of CA 125, and histology did not provide useful prognostic information. Stage, residual disease, minimum CA 125, and CA 125 t 0.5 individually were predictive of persistent disease or recurrence within 3 years of diagnosis with sensitivities of 97, 70, 34, and 49%, respectively, and specificities of 33, 83, 100, and 83%, respectively. When these factors are combined, defining an unfavorable prognostic group as those patients having residual disease greater than 1 cm, CA 125 t 0.5 greater than 12 days, or minimum CA 125 never falling below 35 U/ml, sensitivity and specificity were 96 and 65%, respectively, at 1 year of follow-up and 91 and 75%, respectively, at 3 years of follow-up. Conclusions. In those patients in whom residual small volume disease after primary surgery indicates a good prognosis, minimum CA 125 and CA 125 t 0.5 during chemotherapy can further categorize patients into favorable and unfavorable prognostic groups.
Keywords: Antigens, Tumor-Associated, Carbohydrate; CA 125 half-life tumor markers; CA 125 half‐life tumor markers; Carcinoma; Carcinoma, Endometrioid; Female; Follow-Up Studies; Forecasting; Half-Life; Human; Neoplasm Recurrence, Local; Neoplasm Staging; Ovarian Neoplasms; Prognosis; Retrospective Studies; Risk Factors; Sensitivity and Specificity; Survival Rate; article; ca 125 antigen; cancer grading; cancer recurrence; cancer size; cancer staging; dept.hms; diagnostic accuracy; disease course; epithelial ovarian cancer; female; half life time; histopathology; human; human tissue; major clinical study; ovary carcinoma; priority journal; prognosis; prognostic indicators; retrospective study